Interference of the oscillating glycolysis with the oscillating tryptophan synthesis in the E. coli cells. (4th January 2018) - Maria, Gheorghe; Gijiu, Cristiana Luminita; Maria, Cristina; Tociu, Carmen
Graphical abstract: Highlights: Oscillatory glycolysis interference with cell processes has seldom been investigated. Tryptophan synthesis is an oscillatory metabolic process of high practical interest. Tryptophan synthesis is connected to glycolysis through the phosphoenolpyruvate node. An in silico analysis of this interference in E. coli is performed for the first time. The analysis allows guidance of the tryptophan synthesis bioprocess optimization. Abstract: Autonomous oscillations of glycolytic intermediates' concentrations reflect the dynamics of the control and regulation of this major catabolic pathway in living cells. In spite of its major role in the cell central carbon metabolism (CCM ), glycolysis interference with other metabolic pathways has seldom been investigated. However, the glycolysis model module is the 'core' part of any systematic and structured model-based analysis of the cell metabolism. On the other hand, tryptophan (TRP ) synthesis is another oscillatory metabolic process of high practical interest in the biosynthesis industry, and in medicine. Because theTRP synthesis is strongly connected to the glycolysis through thePEP (phosphoenolpyruvate) node, based on two reduced kinetic models for glycolysis andTRP synthesis, this paper performs, for the first time, an in silico analysis of the way by which the two oscillatory processes interfere in the E. coli cells. The analysis allows guidance of tryptophan synthesis optimization.